Islamic Republic of Afghanistan : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
According to the national household survey conducted during the summer and autumn of 2005, poverty in Afghanistan (headcount rate) is about 33 percent. Economic performance since the fall of the Taliban regime has been strong, and macroeconomic stability has been maintained. During 2002-03 through 2006-07, real GDP growth has averaged 15 percent per year, reflecting a recovery in agriculture, donor-funded postwar reconstruction, and initial yet promising growth of a range of private sector activities. The macroeconomic policy framework is broadly in line with the authorities' economic program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet